Inert anode and preparation method and application thereof

By using an inert anode with a three-layer coating structure of an iron-based alloy matrix and a nickel, precious metals and CeO2 layers in the acid-based aluminum oxide electrolysis, the problem of low current efficiency of the inert electrode is solved, and corrosion resistance and conductivity are improved. It extends service life and reduces costs, and improves the economic and environmental performance of the electrolytic aluminum industry.

CN119221041APending Publication Date: 2024-12-31CHINA SHENHUA ENERGY CO LTD HARWUSU OPEN-PIT COAL MINE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411657372.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The current efficiency of the inert electrode in acid-based aluminum oxide electrolysis is low, and there are problems such as poor corrosion resistance, poor oxidation resistance, short service life and high cost.

Method used

An inert anode consisting of a ferro-based alloy as a matrix, a nickel layer, a noble metal layer (such as ruthenium or rhodium) and a CeO2 layer is prepared by electroplating and calcining to improve the corrosion resistance and conductivity of the electrode. .

Benefits of technology

It significantly improves the stability and current efficiency of the inert anode, extends the service life, reduces production costs, is suitable for highly corrosive environments, and improves the economic benefits and environmental protection performance of the electrolytic aluminum industry.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an inert anode and a preparation method and application thereof. The inert anode is composed of an alloy matrix and three coatings wrapping the alloy matrix, and the three coatings are sequentially a nickel layer, a precious metal layer and a CeO2 layer from inside to outside. The iron-based alloy is adopted as a base body, and the three-layer coating structure of the nickel layer, the precious metal layer and the CeO2 layer is combined, so that the corrosion resistance and the conductivity of the anode can be enhanced. When the inert anode is used for acid electrolysis of aluminum oxide, the service life of the inert anode can be further prolonged, the electrolysis efficiency of the inert anode can be further improved, and the inert anode has important significance in improving the economic benefits and environmental protection performance of the electrolytic aluminum industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery electrodes, and in particular to an inert anode, a preparation method and application thereof. Background Art

[0002] The current Hall-Héroult aluminum electrolysis anode uses carbon material. The reaction of the carbon anode is: Al2O3+3 / 2C→2Al+3 / 2CO2, which leads to a large consumption of carbon anodes. The carbon anode consumed per ton of aluminum exceeds 400kg, making the aluminum electrolysis industry a high-carbon industry. Economically, it is necessary to invest in the construction of a huge carbon anode factory, which increases production costs. In terms of technology, the continuous consumption of carbon anodes can lead to unstable pole distances, and complex mechanical devices are required to adjust the pole distances, which complicates the aluminum electrolysis process; it also leads to the formation of carbon slag in the electrolytic cell, increases the consumption of fluoride salts, and affects the stable operation of the electrolytic cell. In terms of environmental protection, a large amount of CO2 and a small amount of CO, as well as carcinogenic CFn substances, are produced during the electrolysis reaction, which seriously pollutes the atmospheric environment. It is necessary to equip and build a huge flue gas purification system, which increases the production cost of aluminum electrolysis.

[0003] For the above reasons, since the birth of aluminum electrolysis industry, people have been developing inert anodes to replace the currently common carbon anodes (i.e. active anodes), which is considered a revolution in aluminum electrolysis industry. The inert anodes used in aluminum electrolysis industry refer to those anodes that are not consumed or consumed in a small amount in the currently common cryolite-alumina molten salt electrolysis. The inert anode reaction of aluminum electrolysis is: Al2O3→2Al+3 / 2O2.

[0004] There are some differences between the acid-based alumina electrolysis technology and the traditional alkaline-based alumina electrolysis technology. The chemical and physical properties of acid-based alumina are also different from those of traditional alkaline-based alumina. At present, the current efficiency of the acid-based alumina electrolysis technology is lower than that of the alkaline-based alumina electrolysis technology. In order to improve this situation, inert anodes are used instead of traditional carbon anodes. The electrodes are not consumed during the electrolysis process, and no additional carbon processing plant is required, which reduces production costs. Moreover, since the electrodes are not consumed, the pole distance is stable and easy to control, the number of anode replacements is small, and the labor intensity is reduced. A higher anode current density can be used to increase the production capacity of the electrolytic cell. The anode product is oxygen, which avoids environmental pollution and improves the current efficiency of electrolysis.

[0005] At present, inert anode materials are mainly concentrated in three categories: ceramic anodes, metal ceramic anodes and metal alloy anodes. Ceramic anodes have significant advantages in corrosion resistance, high temperature stability, electrochemical inertness, etc. in cryolite melts, but they have poor thermal shock resistance, high brittleness and difficult processing. The conductivity of metal ceramic anode materials needs to be further improved, and there is still the problem of poor thermal shock resistance; in addition, the activity of the ceramic phase and the metal phase in the metal ceramic anode is different. The preferential corrosion of any phase will cause rapid destruction of the electrode, and the corrosion products will also cause pollution and quality degradation of aluminum products.

[0006] The inert anode made of metal material has the advantages of good electrical conductivity, thermal conductivity, thermal shock resistance, low cost and easy connection with the busbar of the anode, but the metal anode has poor oxidation resistance and molten salt corrosion resistance in the molten salt environment of aluminum electrolysis. Precious metals such as rhodium and ruthenium are ideal inert anode materials. Due to the high price of precious metals, they cannot be directly used as inert anodes in industry. Preparing precious metals into coatings is a promising way to utilize the characteristics of precious metals. However, the coated precious metal layer is thin and easily worn and scratched, resulting in high-speed corrosion of the alloy matrix. Therefore, how to obtain an inert anode with a composite structure and good performance is of great significance for the efficient completion of acid-based aluminum electrolysis. Summary of the invention

[0007] The main purpose of the present invention is to provide an inert anode, a preparation method and application thereof, so as to solve the problem of low current efficiency of the inert electrode in the prior art acid-process alumina aluminum electrolysis.

[0008] In order to achieve the above-mentioned object, according to the first aspect of the present invention, an inert anode is provided, which is composed of an alloy substrate and a three-layer coating covering the alloy substrate, wherein the three-layer coating is a nickel layer, a precious metal layer and a CeO2 layer from the inside to the outside.

[0009] Furthermore, the alloy matrix is ​​an iron-based alloy, and the iron-based alloy includes the element Cr, wherein the mass content of the element Cr in the iron-based alloy is 20-30%.

[0010] Furthermore, the thickness of the alloy substrate is 3-5 mm; preferably, the thickness of the nickel layer is 10-50 μm; preferably, the thickness of the CeO2 layer is 1-5 mm.

[0011] Furthermore, the noble metal layer is a ruthenium layer or a rhodium layer; preferably, the thickness of the noble metal layer is 1-5 μm.

[0012] In order to achieve the above-mentioned purpose, according to the second aspect of the present invention, a method for preparing the above-mentioned inert electrode is provided, and the preparation method comprises: subjecting the alloy substrate to pre-plating treatment to obtain the alloy substrate to be plated; subjecting the alloy substrate to be plated to electroplating a nickel layer, electroplating a precious metal layer and calcining a CeO2 layer in sequence to obtain the inert electrode.

[0013] Furthermore, the pre-plating treatment includes: mechanically grinding, ultrasonically cleaning, alkali cleaning and acid cleaning the alloy substrate in sequence; preferably, the electroplating nickel layer includes: immersing the alloy substrate to be plated in a nickel electroplating solution, performing a first electroplating, and completing the electroplating nickel layer treatment; preferably, the electroplating precious metal layer includes: immersing the electrode treated with the electroplated nickel layer in a precious metal solution, performing a second electroplating, and completing the electroplating precious metal layer treatment; preferably, the calcining CeO2 layer includes: after cleaning the electrode treated with the electroplated precious metal layer, applying cerium nitrate on the cleaned electrode surface, and calcining to obtain an inert electrode.

[0014] Further, the nickel electroplating solution is composed of: 200 g / L nickel sulfate and 50 g / L boric acid, with a pH value of 3; preferably, the current density of the first electroplating is 10-15 / A·dm -2 ; Preferably, the temperature of the first electroplating is 60-65°C; Preferably, the time of the first electroplating is 20-40min.

[0015] Furthermore, the noble metal solution is a 65% ruthenium solution or a 60% rhodium solution by mass fraction, and the pH value is 1.5; preferably, the current density of the second electroplating is 0.8-1.0. / A·dm -2 ; Preferably, the temperature of the second electroplating is 55-60°C; Preferably, the time of the second electroplating is 10-15min.

[0016] Furthermore, the cleaning includes: first cleaning the electrode after the electroplating precious metal layer with acetone for 30-40 minutes, and then alkaline washing with 100g / L NaOH solution for 3-4 hours; preferably, the mass fraction of cerium nitrate is 10-15%; preferably, the calcination temperature is 500-550°C; preferably, the calcination time is 5-5.5h.

[0017] In order to achieve the above-mentioned purpose, according to the third aspect of the present invention, there is provided an application of an inert electrode prepared by the above-mentioned preparation method in an acid-based alumina electrolysis process.

[0018] By applying the technical solution of the present invention, an iron-based alloy is used as a substrate, and a three-layer coating structure of a nickel layer, a noble metal layer and a CeO2 layer is combined to enhance the corrosion resistance and conductivity of the anode. When the inert anode of the present application is used for acid electrolysis of aluminum oxide, its service life and current efficiency can be further improved, which is of great significance to improving the economic benefits and environmental protection performance of the electrolytic aluminum industry. DETAILED DESCRIPTION

[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0020] As mentioned in the background technology, although the inert electrode used in the prior art can improve the efficiency of aluminum electrolysis compared with the carbon electrode, it still has problems such as poor corrosion resistance, poor oxidation resistance, short service life, and high cost, which leads to the current efficiency of the inert electrode in practical applications being unable to meet higher application requirements. Therefore, the present application intends to provide an inert electrode with better electrode performance.

[0021] In a first typical embodiment of the present application, an inert anode is provided, which is composed of an alloy substrate and a three-layer coating covering the alloy substrate, wherein the three-layer coating is a nickel layer, a precious metal layer and a CeO2 layer from the inside to the outside.

[0022] The inert electrode of the present application has a multilayer structure, which can improve the corrosion resistance and oxidation resistance of the electrode. Specifically, the nickel layer acts as a transition layer to improve the bonding strength between the alloy matrix and the precious metal layer; the precious metal layer has excellent electrocatalytic properties and can effectively reduce the overpotential during the electrolysis process; the CeO2 layer acts as a protective layer, which can effectively prevent the anode from being oxidized and corroded during the electrolysis process. This design not only improves the corrosion resistance of the anode, but also enhances its electrical conductivity, so that the stability and current efficiency of the inert anode are significantly improved during the acid-based aluminum oxide electrolysis process.

[0023] In order to further improve the thermal stability, oxidation resistance and corrosion resistance of the inert electrode, the chromium content in the alloy matrix is ​​adjusted to a suitable range. In a preferred embodiment, the alloy matrix is ​​an iron-based alloy, and the iron-based alloy includes the element Cr, wherein the mass content of the element Cr in the iron-based alloy is 20-30%. By adjusting the Cr content, the inert electrode is more stable in an acidic environment, the service life of the anode is extended, and it is suitable for the environment of acid-based aluminum electrolysis.

[0024] In order to further improve the mechanical strength and electrochemical properties of the inert electrode, in a preferred embodiment, the thickness of the alloy substrate is 3-5 mm; preferably, the thickness of the nickel layer is 10-50 μm, which is a pure metal element; preferably, the thickness of the CeO2 layer is 1-5 mm.

[0025] The noble metal layer can improve the electrocatalytic activity of the inert electrode. In a preferred embodiment, the noble metal layer is a ruthenium layer or a rhodium layer, both of which are single metals; preferably, the thickness of the noble metal layer is 1-5 μm.

[0026] In a second typical embodiment of the present application, a method for preparing the above-mentioned inert electrode is provided, the method comprising: performing a pre-plating treatment on the alloy substrate to obtain an alloy substrate to be plated; performing electroplating of a nickel layer, electroplating of a precious metal layer and calcining of a CeO2 layer on the alloy substrate to obtain an inert electrode. Through the above-mentioned preparation steps, the close combination of each coating and the substrate can be promoted, so that the properties of each coating can be better exerted, and the integrity and stability of each layer can be ensured.

[0027] In order to further improve the bonding tightness and uniformity of each coating, in a preferred embodiment, the pre-plating treatment includes: mechanically grinding, ultrasonic cleaning, alkaline cleaning and acid cleaning of the alloy substrate in sequence; preferably, the electroplating nickel layer includes: immersing the alloy substrate to be plated in a nickel electroplating solution, performing a first electroplating, and completing the electroplating nickel layer treatment; preferably, the electroplating precious metal layer includes: immersing the electrode treated with the electroplated nickel layer in a precious metal solution, performing a second electroplating, and completing the electroplating precious metal layer treatment; preferably, the calcining CeO2 layer includes: after cleaning the electrode treated with the electroplated precious metal layer, applying cerium nitrate on the cleaned electrode surface, and calcining to obtain an inert electrode.

[0028] Among them, since there are inevitably oxide layers and oil layers on the surface of the alloy substrate, pre-plating treatment is necessary to obtain a coating with good bonding strength. Alkaline washing can remove the oil layer, and acid washing can remove the oxide layer.

[0029] In order to further obtain a nickel layer with uniform plating and high bonding strength, in a preferred embodiment, the composition of the nickel electroplating solution is: 200 g / L nickel sulfate and 50 g / L boric acid, with a pH value of 3; preferably, the current density of the first electroplating is 10-15 / A·dm -2 ; Preferably, the temperature of the first electroplating is 60-65°C; Preferably, the time of the first electroplating is 20-40min.

[0030] To further improve the electrocatalytic efficiency of the inert electrode, in a preferred embodiment, the noble metal solution is a 65% ruthenium solution or a 60% rhodium solution by mass fraction, and the pH value is 1.5; preferably, the current density of the second electroplating is 0.8-1.0 / A·dm-2 ; Preferably, the temperature of the second electroplating is 55-60°C; Preferably, the time of the second electroplating is 10-15min.

[0031] In order to further ensure the compactness and stability of the CeO2 layer and improve the corrosion resistance of the inert electrode, in a preferred embodiment, the cleaning includes: first cleaning the electrode after the electroplating precious metal layer with acetone for 30-40 minutes, and then alkali washing with 100g / L NaOH solution for 3-4 hours; preferably, the mass fraction of cerium nitrate is 10-15%; preferably, the calcination temperature is 500-550℃; preferably, the calcination time is 5-5.5h.

[0032] In a third typical embodiment of the present application, an application of an inert electrode prepared by the above-mentioned preparation method in an acid-process aluminum oxide electrolysis process is provided. The above-mentioned inert anode has good tolerance to its high acid environment in the acid-process aluminum oxide electrolysis, which can not only significantly reduce the energy consumption in the electrolysis process and improve the electrolysis efficiency, but also effectively reduce the maintenance cost of the electrolytic cell and extend its service life.

[0033] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0034] Example 1

[0035] The specific steps for preparing the inert electrode of this embodiment are as follows:

[0036] The alloy substrate is an iron-based alloy with a Cr content of 20% by mass and a thickness of 4 mm. First, the alloy substrate is pre-treated, including mechanical grinding to remove the surface oxide layer and dirt, followed by ultrasonic cleaning to further remove tiny impurities, and then alkaline washing with 100g / L NaOH solution for 3.5 hours to neutralize any residual acidic substances and deeply clean the surface. Finally, 5g / L H2SO4 is used for pickling for 2 hours. This step is intended to remove the oxide film on the surface of the alloy substrate to activate the surface of the alloy substrate in preparation for the subsequent electroplating process.

[0037] The nickel layer was electroplated by placing the alloy substrate into a nickel electroplating solution (pH 3) containing 200 g / L nickel sulfate and 50 g / L boric acid for the first electroplating at a temperature of 63°C and a current density of 15 A / dm 2 , time is 30min, to complete the electroplating of the nickel layer, and the obtained nickel layer thickness is 30μm.

[0038] The precious metal layer was electroplated, and the electrode after the nickel layer was electroplated was immersed in a ruthenium solution with a mass fraction of 65% (pH value of 1.5) for the second electroplating. The temperature was set at 58°C and the current density was 0.8A / dm 2 , time is 12 minutes to complete the electroplating of the precious metal layer, and the thickness of the precious metal layer obtained is 3μm.

[0039] The CeO2 layer was calcined, and the electrode after the electroplating of the precious metal layer was cleaned, first using acetone ultrasonic cleaning for 35 minutes, and then using 100g / L NaOH solution for alkaline cleaning for 3.5 hours. Subsequently, a 10% mass fraction of cerium nitrate solution was evenly applied to the cleaned electrode surface. The electrode was calcined at a temperature of 500°C for 5 hours to form a CeO2 layer with a thickness of 3mm, and finally the inert electrode of the present application was obtained.

[0040] The above-mentioned inert electrode is used as the anode and the graphite crucible is used as the cathode. The specific composition of the electrolyte is as follows in terms of mass percentage: 30% AlF3, 35% K3AlF6, and 35% Na3AlF6. 5% acid-process alumina is electrolyzed at 900°C, and the current efficiency under this state is 95% as detected by the inventory method.

[0041] Example 2

[0042] The specific steps for preparing the inert electrode of this embodiment are as follows:

[0043] The alloy substrate is an iron-based alloy with a Cr mass content of 30% and a thickness of 5 mm. First, the alloy substrate is pre-treated, including mechanical grinding to remove the surface oxide layer and dirt, followed by ultrasonic cleaning to further remove tiny impurities, and then alkaline washing with 100g / L NaOH solution for 3.5 hours to neutralize any residual acidic substances and deeply clean the surface. Finally, 5g / L H2SO4 is used for pickling for 2 hours. This step is intended to remove the oxide film on the surface of the alloy substrate to activate the surface of the alloy substrate in preparation for the subsequent electroplating process.

[0044] The nickel layer was electroplated by placing the alloy substrate into a nickel electroplating solution (pH 3) containing 200 g / L nickel sulfate and 50 g / L boric acid for the first electroplating at a temperature of 60°C and a current density of 10 A / dm 2 , time is 40min, to complete the electroplating of the nickel layer, and the thickness of the obtained nickel layer is 40μm.

[0045] The precious metal layer was electroplated, and the electrode after the nickel layer was electroplated was immersed in a 60% rhodium solution (pH 1.5) for the second electroplating, the temperature was set at 55°C, the current density was 1.0A / dm2 , time is 10 minutes to complete the electroplating of the precious metal layer, and the thickness of the precious metal layer obtained is 5μm.

[0046] The CeO2 layer was calcined, and the electrode after the electroplating of the precious metal layer was cleaned, first using acetone ultrasonic cleaning for 30 minutes, and then using 100g / L NaOH solution for alkaline cleaning for 3.0 hours. Subsequently, a cerium nitrate solution with a mass fraction of 12% was evenly applied to the cleaned electrode surface. The electrode was calcined at a temperature of 525°C for 5.0 hours to form a CeO2 layer with a thickness of 5mm, and finally the inert electrode of the present application was obtained.

[0047] The above-mentioned inert electrode was used as the anode and the graphite crucible was used as the cathode. The specific composition of the electrolyte, in terms of mass percentage, was as follows: 30% AlF3, 35% K3AlF6, and 35% Na3AlF6. 5% acid-process alumina was electrolyzed at 900°C, and the current efficiency under this state was 94.5% as measured by the inventory method.

[0048] Example 3

[0049] The specific steps for preparing the inert electrode of this embodiment are as follows:

[0050] The alloy substrate is an iron-based alloy with a Cr mass content of 25% and a thickness of 3 mm. First, the alloy substrate is pre-treated, including mechanical grinding to remove the surface oxide layer and dirt, followed by ultrasonic cleaning to further remove tiny impurities, and then alkaline washing with 100g / L NaOH solution for 3.5 hours to neutralize any residual acidic substances and deeply clean the surface. Finally, 5g / L H2SO4 is used for pickling for 2 hours. This step is intended to remove the oxide film on the surface of the alloy substrate to activate the surface of the alloy substrate in preparation for the subsequent electroplating process.

[0051] The nickel layer was electroplated by placing the alloy substrate into a nickel electroplating solution (pH 3) containing 200 g / L nickel sulfate and 50 g / L boric acid for the first electroplating at a temperature of 65°C and a current density of 10 A / dm 2 , time is 20min, to complete the electroplating of the nickel layer, and the obtained nickel layer thickness is 50μm.

[0052] The precious metal layer was electroplated, and the electrode after the nickel layer was electroplated was immersed in a ruthenium solution with a mass fraction of 65% (pH value of 1.5) for the second electroplating. The temperature was set at 60°C and the current density was 0.8A / dm 2 , time is 15min, to complete the electroplating of the precious metal layer, and the thickness of the precious metal layer obtained is 1μm.

[0053] The CeO2 layer was calcined, and the electrode after the electroplating of the precious metal layer was cleaned, first using acetone ultrasonic cleaning for 35 minutes, and then using 100g / L NaOH solution for alkaline cleaning for 3.0 hours. Subsequently, a 10% mass fraction of cerium nitrate solution was evenly applied to the cleaned electrode surface. Calcination was performed at a temperature of 550°C for 5.5 hours to form a CeO2 layer with a thickness of 1mm, and finally the inert electrode of the present application was obtained.

[0054] The above-mentioned inert electrode is used as the anode and the graphite crucible is used as the cathode. The specific composition of the electrolyte is as follows in terms of mass percentage: 30% AlF3, 35% K3AlF6, and 35% Na3AlF6. 5% acid-process alumina is electrolyzed at 1000°C, and the current efficiency under this state is 95.5% as detected by the inventory method.

[0055] Comparative Example 1

[0056] The same operations as in Example 1 are used to perform pre-plating treatment, electroplating nickel layer treatment and electroplating precious metal layer treatment on the same alloy substrate in Example 1 to obtain an inert electrode having a structure of an alloy substrate, a nickel layer and a precious metal ruthenium layer from the inside to the outside. The inert electrode obtained above is used as an anode and a graphite crucible is used as a cathode. The specific composition of the electrolyte, in terms of mass percentage, is as follows: 30% AlF3, 35% K3AlF6, and 35% Na3AlF6. 5% acid-process alumina is electrolyzed at 1000°C with a current efficiency of 92%.

[0057] Comparative Example 2

[0058] The same operations as in Example 1 are used to carry out pre-plating treatment, electroplating nickel layer treatment and calcination CeO2 layer treatment on the same alloy substrate in Example 1 to obtain an inert electrode having a structure of an alloy substrate, a nickel layer and a CeO2 layer from the inside to the outside. The inert electrode obtained above is used as an anode and a graphite crucible is used as a cathode. The specific composition of the electrolyte, in terms of mass percentage, is as follows: 30% AlF3, 35% K3AlF6, and 35% Na3AlF6. When 5% acid-process alumina is electrolyzed at 1000°C, the conductivity deteriorates and the current efficiency is 90%.

[0059] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects: the inert electrode of the present application uses an iron-based alloy as a matrix, combined with a three-layer coating structure of a nickel layer, a noble metal layer and a CeO2 layer, which can enhance the corrosion resistance and conductivity of the anode. In the process of acid-based aluminum oxide electrolysis, the stability and efficiency of the inert anode are significantly improved, and it is suitable for various industrial electrolytic cells, especially when dealing with highly corrosive electrolytes, which is of great significance to improving the economic benefits and environmental protection performance of the electrolytic aluminum industry.

[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An inert anode, characterized in that: The inert anode is composed of an alloy substrate and a three-layer coating covering the alloy substrate. The three coating layers are a nickel layer, a precious metal layer and a CeO2 layer from the inside to the outside.

2. The inert anode according to claim 1, characterized in that The alloy matrix is ​​an iron-based alloy, and the iron-based alloy includes the element Cr, wherein the mass content of the element Cr in the iron-based alloy is 20-30%.

3. The inert anode according to claim 1, characterized in that The thickness of the alloy matrix is ​​3-5 mm; Preferably, the thickness of the nickel layer is 10-50 μm; Preferably, the thickness of the CeO2 layer is 1-5 mm.

4. The inert anode according to claim 1, characterized in that The noble metal layer is a ruthenium layer or a rhodium layer; Preferably, the thickness of the noble metal layer is 1-5 μm.

5. The method for preparing the inert anode according to any one of claims 1 to 4, characterized in that: The preparation method comprises: The alloy substrate is subjected to a pre-plating treatment to obtain an alloy substrate to be plated; The alloy substrate to be plated is subjected to electroplating of a nickel layer, electroplating of a noble metal layer and calcining of a CeO2 layer in sequence to obtain the inert electrode.

6. The preparation method according to claim 5, characterized in that: The pre-plating treatment includes: mechanical grinding, ultrasonic cleaning, alkali cleaning and acid cleaning of the alloy substrate in sequence; Preferably, the electroplating of the nickel layer comprises: immersing the alloy substrate to be plated in a nickel electroplating solution, performing a first electroplating, and completing the electroplating of the nickel layer; Preferably, the electroplating of the precious metal layer comprises: immersing the electrode treated with the electroplated nickel layer in a precious metal solution, performing a second electroplating, and completing the electroplating of the precious metal layer; Preferably, the calcining of the CeO2 layer comprises: cleaning the electrode treated with the electroplated precious metal layer, coating cerium nitrate on the surface of the cleaned electrode, and calcining to obtain the inert anode.

7. The preparation method according to claim 6, characterized in that: The nickel electroplating solution is composed of: 200 g / L nickel sulfate and 50 g / L boric acid, with a pH value of 3; Preferably, the current density of the first electroplating is 10-15 / A·dm -2 ; Preferably, the temperature of the first electroplating is 60-65°C; Preferably, the first electroplating time is 20-40 minutes.

8. The preparation method according to claim 6, characterized in that: The noble metal solution is a 65% ruthenium solution or a 60% rhodium solution by mass fraction, and the pH value is 1.5; Preferably, the current density of the second electroplating is 0.8-1.

0. / A·dm -2 ; Preferably, the temperature of the second electroplating is 55-60°C; Preferably, the second electroplating time is 10-15 minutes.

9. The preparation method according to claim 6, characterized in that: The cleaning comprises: first cleaning the electrode after the electroplating of the precious metal layer with acetone for 30-40 minutes, and then alkaline cleaning with 100g / L NaOH solution for 3-4 hours; Preferably, the mass fraction of the cerium nitrate is 10-15%; Preferably, the calcination temperature is 500-550°C; Preferably, the calcination time is 5-5.5h.

10. Use of the inert electrode prepared by the preparation method according to any one of claims 5 to 9 in an acid-based alumina electrolysis aluminum process.